Investigating the fatigue performance of Nano-Silica-modified concrete with various admixtures: An experimental study - Sajjad Shokouh; Kamran Goshtasbi; Hamid Reza Nejati; Javad Karimi; Arsham Moayedi Far (Results in Engineering)
Understanding the fatigue behavior of concrete structures under cyclic loading is crucial for enhancing their durability and performance in demanding applications. In this study, four types of concrete mixtures containing varying percentages of Nano-Silica (NS) (0.0 %, 0.5 %, 1.0 %, and 1.5 %) were prepared to evaluate their mechanical properties and fatigue performance. The investigation focused on assessing the monotonic tensile and compressive behavior, as well as the tensile fatigue life, to establish the relationship between NS content, mechanical properties, and fatigue resistance. Key findings indicate that the optimal NS content for enhancing uniaxial compressive strength (UCS), tensile strength (σt), and elastic modulus (E) was 1.0 %. However, fatigue life under cyclic tensile loading decreased with increasing NS content due to the increased brittleness (B) introduced by higher strength mixtures. Secondary strain rate analysis and brittleness index (BI) calculations further highlighted the balance between mechanical enhancement and deformation capacity. These results provide valuable insights into the design of NS-modified concrete for applications requiring a balance between strength and fatigue durability under extreme loading conditions.